1993
DOI: 10.1152/jappl.1993.75.5.2142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thoracoabdominal calibration methods in normal human subjects

Abstract: In 19 normal subjects in the supine posture, we compared accuracy and precision of calibration methods that utilized different ranges of tidal volumes and thoracoabdominal partitioning: spontaneous quiet breathing (QB), isovolume maneuvers, and voluntary efforts to breathe with variable tidal volume and thoracoabdominal partitioning. Thoracic and abdominal movements were measured with the respiratory area fluxometer. Calibration methods utilizing one or more types of respiratory efforts were applied to three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…Unfortunately, the RespiEvents™ software does not allow the user to access the exclusion criteria, or assess the intrinsic variability of the RIP signals during the calibration period. This made it impossible to assess whether the relative contribution of the rc and abd compartments to VT was sufficiently variable during the 5 min of QDC calibration to derive robust coefficients in these anaesthetised infants [12]. The QDC method also assumes that the respiratory system can be represented by a single compartment model, with instantaneous pressure equilibration throughout the system, which may prove to be a significant limitation in infants.…”
Section: Validation Of Qdc Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the RespiEvents™ software does not allow the user to access the exclusion criteria, or assess the intrinsic variability of the RIP signals during the calibration period. This made it impossible to assess whether the relative contribution of the rc and abd compartments to VT was sufficiently variable during the 5 min of QDC calibration to derive robust coefficients in these anaesthetised infants [12]. The QDC method also assumes that the respiratory system can be represented by a single compartment model, with instantaneous pressure equilibration throughout the system, which may prove to be a significant limitation in infants.…”
Section: Validation Of Qdc Methodsmentioning
confidence: 99%
“…In an attempt to overcome this problem, various modifications of the isovolume technique have been proposed for use in infants and children, including the use of different patterns of ventilation, due to changes in body posture, sleep state or airway occlusion, to derive the relative contribution of the rc and abd to the tidal volume and thereby assign appropriate calibration coefficients [4,5,[10][11][12][13]. Nevertheless, these methods generally remain too complex for widespread use.…”
Section: Validation Of Respiratory Inductive Plethysmography Using Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a study conducted by Sartene et al (7) demonstrated that, during quiet breathing, there is dispersion of approximately 20% of the mean tidal volume, and only 8% of this value corresponds to the contribution of the thoracic and abdominal compartments. Therefore, the authors stated that the use of calibrations requiring quiet breathing is questionable when quiet breathing is employed in devices with two degrees of freedom, given that most of the study participants, when evaluated in the supine position, predominantly used only one degree of freedom.…”
Section: Discussionmentioning
confidence: 97%
“…(2)(3)(4)(5)(6)(7) The QDC method is performed during a given period of baseline breathing and uses a statistical placed horizontally on a stretcher, lying on their backs, with the hips and knees flexed; for the sitting position, the volunteers were sat on a chair without back support, with the hips and knees at a 90° angle; and for the orthostatic position, the volunteers were instructed to stand upright, with arms relaxed at their sides, and distribute their body weight evenly on both legs (Figure 1).…”
Section: Introductionmentioning
confidence: 99%